FGF2 is an endogenous regulator of alcohol reward and consumption. (18th November 2021) - Even‐Chen, Oren; Herburg, Leonie; Kefalakes, Ekaterini; Urshansky, Nataly; Grothe, Claudia; Barak, Segev
Abstract: Alcohol use disorder (AUD) is a chronic, relapsing disorder, characterized by escalating alcohol drinking and loss of control, with very limited available treatments. We recently reported that the expression of fibroblast growth factor 2 ( Fgf2 ) is increased in the striatum of rodents following long‐term excessive alcohol drinking and that the systemic or intra‐striatal administration of recombinant FGF2 increases alcohol consumption. Here, we set out to determine whether the endogenous FGF2 plays a role in alcohol drinking and reward, by testing the behavioural phenotype of Fgf2 knockout mice. We found that Fgf2 deficiency resulted in decreased alcohol consumption when tested in two‐bottle choice procedures with various alcohol concentrations. Importantly, these effects were specific for alcohol, as a natural reward (sucrose) or water consumption was not affected by Fgf2 deficiency. In addition, Fgf2 knockout mice failed to show alcohol‐conditioned place preference (CPP) but showed normal fear conditioning, suggesting that deletion of the growth factor reduces alcohol's rewarding properties. Finally, Fgf2 knockout mice took longer to recover from the loss of righting reflex and showed higher blood alcohol concentrations when challenged with an intoxicating alcohol dose, suggesting that their ethanol metabolism might be affected. Together, our results show that the endogenous FGF2 plays a critical role in alcohol drinking and reward and indicate that FGF2 is a positive regulator of alcohol‐drinking behaviours. Our findings suggest that FGF2 is a potential biomarker for problem alcohol drinking and is a potential target for pharmacotherapy development for AUD. Abstract : We show that knockout of the Fgf2 gene leads to decreased alcohol consumption, without affecting sucrose intake. In addition, Fgf2 deficient mice showed impaired alcohol reward and a longer reaction to the hypnotic effects of alcohol at a high dose. Together, our results suggest that FGF2 is a positive regulator of alcohol‐drinking behaviours and that FGF2 is a potential biomarker for problem alcohol drinking and is a potential target for pharmacotherapy development.